The avian remains from El Juyo, Lower Magdalenian Cantabrian Spain - Rufà, Anna (2022)
El Juyo is one of the Cantabrian sites of Iberia known from long ago for its important Lower Magdalenian sequence. The present study reports the results of the zooarchaeological and taphonomic analysis of the avian remains recovered at the site, which complements the archaeological and palaeoecological data already avail-able. The remains recovered are limited, but they seem to indicate that humans were the main accumulating agent in the site, with sporadic presence of owls' activity. Additionally, humans could have used birds for other purposes than as a dietary resource, as suggested by cut marks observed on two wing bones.